2020
DOI: 10.1021/acs.analchem.0c02118
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Microextraction Fiber in Face Mask for in Vivo Sampling and Direct Mass Spectrometry Analysis of Exhaled Breath Aerosol

Abstract: Molecular analysis of exhaled breath aerosol (EBA) with simple procedures represents a key step in clinical and point-of-care applications. Due to the crucial health role, a face mask now is a safety device that helps protect the wearer from breathing in hazardous particles such as bacteria and viruses in the air; thus exhaled breath is also blocked to congregate in the small space inside of the face mask. Therefore, direct sampling and analysis of trace constituents in EBA using a face mask can rapidly provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 32 publications
1
64
0
Order By: Relevance
“…Solid-phase microextraction (SPME) technique is commonly used for VOCs sampling for MS analysis. For example, Yuan et al [ 55 ] demonstrated the collection and enrichment of numerous breath metabolites from EBA using facemask-based microextraction technique (SPME-in-mask) followed by detection using MS with ambient ionization and GC–MS (Fig. 3 ).…”
Section: Ms-based Multidimensional Breath Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Solid-phase microextraction (SPME) technique is commonly used for VOCs sampling for MS analysis. For example, Yuan et al [ 55 ] demonstrated the collection and enrichment of numerous breath metabolites from EBA using facemask-based microextraction technique (SPME-in-mask) followed by detection using MS with ambient ionization and GC–MS (Fig. 3 ).…”
Section: Ms-based Multidimensional Breath Analysismentioning
confidence: 99%
“…Wearable facemask sampling also is convenient for a long-time sampling even many hours in daily life, enabling enrichment of ultrarace VOCs. In addition, facemask could also protect humans from air pollutants in the ambient during the sampling process [ 55 ]. These new features have practical relevance for diagnosing COVID-19, because the breath sample is not easily handling due to their infectiousness.…”
Section: Ms-based Multidimensional Breath Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This offers a novel potential route of breath sampling. Yuan et al inserted SPME fibers into face masks for the collection of exhaled breath aerosol, followed by direct analysis using DART‐MS 46 . Numerous ions related to diet and lifestyle habits were detected, such as protonated nicotine and cotinine derived from tobacco use at m/z 163 and 177, respectively.…”
Section: Applications Of Ambient Ionization Mass Spectrometrymentioning
confidence: 99%
“…While this essentially represents a noninvasive approach for characterization human exhaled breath, still additional sampling via SPME and analysis using DART-MS is needed. 16 Analytical procedures classifying surgical face masks without any sample preparation remain rare. [16][17][18][19] Staff in hospitals or clinics, nursing homes and paramedics are subject to a signi cant risk of infection or contagion demanding for the particularly rapid and reliable detection of SARS-CoV-2, or other pathogens.…”
Section: Introductionmentioning
confidence: 99%